FDG PET of the brain to screen for neurodegenerative disease in older liver transplant candidates. - Jones, Natalie; Schwartz, Trent M.; Bishay, Steven; Robb, W. Hudson; Sams, Amanda; Kogan, Josh; Nable, Monica; Nelson, Sydney; Zhao, Oliver S.; Hohman, Timothy; Huang, Steven; Martinez, Felipe; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: The aging liver transplant population presents new challenges in distinguishing irreversible, age-related causes of dementia from hepatic encephalopathy (HE), given their overlapping clinical presentations. Dementia is often assessed through neuropsychological testing (NPT), but imaging utilizing biomarkers like Fluorodeoxyglucose (FDG) Positron Emission Tomography/Computed Tomography (PET/CT) has been considered as an alternative. This preliminary investigation aims to assess FDG PET/CT in screening for irreversible causes of dementia in older liver transplant candidates. Methods: Eighteen patients with clinical suspicion for dementia during transplant evaluation were assessed using FDG PET/CT of the brain. Demographic data, FDG PET/CT and NPT results, and time between date of order and interpretation of FDG PET/CT and NPT were collected. Concordance between and time-to-diagnosis of FDG PET/CT and NPT were calculated. FDG PET/CT of these patients were compared to healthy, age-matched controls to determine altered patterns of FDG uptake in the brains of these patients. Results: 40% of patients were diagnosed with an irreversible cause of dementia on FDG PET/CT. There was moderate agreement (K = 0.44) between NPT and FDG PET/CT. FDG PET/CT had a sensitivity and specificity of 100% and 50%, respectively. Time-to-diagnosis was significantly shorter with FDG PET/CT (12.4 days) compared to NPT (73.1 days). Voxel-wise analysis showed statistically significant diffuse cortical and basal ganglia hypometabolism in patients being evaluated for liver transplant versus age-matched healthy controls. Conclusion: FDG PET/CT is helpful in screening for irreversible causes of dementia in older liver transplant candidates, but a positive PET indicates that further evaluation is required before denying a patient a potentially life-saving treatment. Efficient workup for these patients is crucial, and FDG PET/CT could provide a sensitive first screening test for dementia in older patients undergoing liver transplant evaluation which can be confirmed with NPT or with more specific biomarkers of neurodegenerative disease. Clinical trial registration: Not applicable.